A Parceria Transatlântica de Comércio e Investimento (TTIP): Uma Negociação Interminável - Fernandes, José Pedro Teixeira (Journal of Business and Legal Sciences / Revista de Ciências Empresariais e Jurídicas, 2017)
The main objective of this article is to review the proposals in negotiation under the TTIP looking both at the arguments that favour the agreement, and to the criticism made by its detractors. To this end, there will be a brief contextualization within the framework of the Atlantic relations of the last decades, and an overview of the subjects under negotiation. Then, a view with some detail, to specific aspects of TTIP for its potential relevance. This is the case of transatlantic cooperation on regulation and recourse to arbitration for international investors. There will be also some reflections on the expected impact on European and US economy. Finally, there will be a brief scrutiny of the strength of geopolitical arguments that favour TTIP, and the obstacles to the future negotiations and the conclusion of the agreement.